Learning Strategies to Develop Students Critical Thinking Skills: A Literature Review - Siti Zalika ROSLY (Communications of International Proceedings, 2021)
Critical thinking is defined as an investigation whose purpose is to explore a situation, phenomenon, question or problem to arrive at a hypothesis or conclusion about it that integrates all available information and that can therefore be convincingly justified (Kurfiss, 1988). It is one of the identified goals of higher education, hence demonstrating its significance in students’ capability portfolio. This skill allows students to be competent in solving problems as well as revealing new discoveries in various education fields (Sutiani et al, 2020). It plays a crucial role in students’ academic performance, as well as in the world of work that follow. Therefore, it is crucial to employ the best method in developing critical thinking skills among students. This paper attempts to explore the effectiveness of two different learning strategies in developing students critical thinking skill; (1) Problem-based learning, and (2) Guided inquiry learning, (Rejeki at el, 2021). Both methods provide valuable input to be included in the teaching and learning process for students pursuing professional accounting education.
Keywords: Critical thinking skills; problem-based learning; guided inquiry learning